Perspectivism of the Renaissance Thought - Menčik, David (Epistēmēs Metron Logos, 2020)
The starting point of the essay is clarifying the difference between the mono-perspective and multi-perspective vision of reality. Off-course the terms perspective, mono-perspective and multi-perspective are not self-explanatory and the meanings of these terms need to be formally analysed. After making the formal difference between mono-perspective thinking and multi-perspective thinking a content difference needs to be made. Namely, why is the Renaissance vision of reality multi-perspective and the Middle-Age vision of reality mono-perspective? The answer to this question needs to be given by the analysis of the original works of the Renaissance thinkers. Our undertaking will not be limited in analysing only one discourse but following the subject from a methodological point of view in a multi-perspectivism way. Therefore, three different discourses will be analysed: The discourse of philosophical anthropology with Mirandola’s vision of man as a paradigmatic example- The discourse of philosophy of nature, with Bruno’s vision of the universe as a paradigmatic example- The discourse of art history in which four paintings will be analysed: these paintings can be considered of having philosophical, value because they provide a picturesque representation of what the Renaissance “world” was really like.